Genotypic and phenotypic predictors of complete heart block and recovery of conduction after surgical repair of congenital heart disease - Murray, Laura E.; Smith, Andrew H.; Flack, English C.; Crum, Kim; Owen, Jill; Kannankeril, Prince J. (Heart rhythm, 2017)
Complete heart block (CHB) is a major complication that occurs after congenital heart surgery. We hypothesized that genetic and clinical factors are associated with the development of postoperative CHB and recovery of atrioventricular (AV) conduction. The purpose of this study was to identify predictors of CHB and recovery after congenital heart surgery. Patients undergoing congenital heart surgery at our institution from September 2007 through June 2015 were prospectively enrolled in a parent study of postoperative arrhythmias. Patients with onset of CHB within 48 hours postoperatively were included in the study. Daily rhythm assessment was performed until demonstration of 1:1 conduction or pacemaker implantation. Of 1199 subjects enrolled, 56 (4.7%) developed postoperative CHB. In multivariate analysis, preoperative digoxin exposure (odds ratio [OR] 2.4, 95% confidence interval [CI] 1.3–4.4), aortic cross-clamp time (OR 1.08, 95% CI 1.04–1.11), ventricular septal defect closure (OR 2.2, 95% CI 1.2–4.1), and a common polymorphism in the gene encoding connexin-40 (GJA5 rs10465885 TT genotype; OR 2.1, 95% CI 1.2–3.8) were independently associated with postoperative CHB. Junctional acceleration (JA) (OR 4.0, 95% CI 1.1–15.1) and intermittent conduction noted during complete AV block (OR 9.1, 95% CI 1.0–80) were independently associated with 1:1 AV conduction recovery. Use of a multivariate model including both JA and intermittent conduction demonstrated good discrimination with a positive predictive value of 86% (95% CI 67%–96%) in predicting 1:1 conduction recovery. Preoperative factors, including a missense polymorphism in GJA5, are independently associated with increased risk for CHB. JA and intermittent conduction may prove useful in predicting recovery of AV conduction among patients with CHB after congenital heart surgery.